2002
DOI: 10.1034/j.1600-0889.2002.201312.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi-box model study of the role of the biospheric metabolism in the recent decline of delta18O in atmospheric CO2

Abstract: From around 1993 to 1997, the NOAA‐CU δ18O measurements at Pt. Barrow, Mauna Loa, Cape Kumukahi, Cape Grim and the South Pole show a decrease in atmospheric CO2δ18O of about 0.5‰. Recently, Gillon and Yakir (2001) have attributed this decrease to a conversion of C3 forests to C4 grasslands through anthropogenic land‐use change. However, their explanation can account for only about 0.02‰ yr−1 decrease rate. In this paper we offer a viable alternative explanation. We have used a multi‐box model of the global car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…558% (55 data sets, R 2 = 0.18, P < 0.01). The estimated d s for 18 O (À7.662 ± 2.113)% at WLG is in agreement with a mean source or sink where the 18 O of CO 2 is in equilibrium with soil water (varying from À9 to À2%)[Ishizawa et al, 2002]. Thus, though subject to a large degree of uncertainty due to relatively poor linear relationship (R 2 < 0.2) compared to that of the d 13 C and CO 2 relationship, the observed d 18 O seasonal cycle is most likely a result of the exchange of atmospheric CO 2 with soil water throughout the year.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…558% (55 data sets, R 2 = 0.18, P < 0.01). The estimated d s for 18 O (À7.662 ± 2.113)% at WLG is in agreement with a mean source or sink where the 18 O of CO 2 is in equilibrium with soil water (varying from À9 to À2%)[Ishizawa et al, 2002]. Thus, though subject to a large degree of uncertainty due to relatively poor linear relationship (R 2 < 0.2) compared to that of the d 13 C and CO 2 relationship, the observed d 18 O seasonal cycle is most likely a result of the exchange of atmospheric CO 2 with soil water throughout the year.…”
supporting
confidence: 75%
“…[17] As cited [Flanagan et al, 1997;Friedli et al, 1987;Ishizawa et al, 2002;Keeling, 1961;Mook et al, 1983;Nakazawa et al, 1997b;Trolier et al, 1996] and discussed above, d 18 O in atmospheric CO 2 is determined by exchange with vegetation, leafwater, soils and the ocean. It is the exchange of CO 2 with the terrestrial biosphere (through ecosystem photosynthesis and respiration) that drives much of the seasonal variation in the d 18 O of atmospheric CO 2 , especially over the continental NH.…”
Section: Resultsmentioning
confidence: 99%
“…[33] D A affects significantly the seasonal variation of d 18 O of atmospheric CO 2 inside the canopy, because its seasonal changes are larger than those of D R , A and R. To estimate D A accurately, it is important to know the ratio (r) of the assimilated CO 2 flux to the back diffusion CO 2 flux for photosynthesis and its seasonality, which are uncertain at present. Recently, Ishizawa et al [2002] also suggested that the secular declines of about 0.5% in d 18 O of atmospheric CO 2 measured at Pt. Barrow, Mauna Loa, Cape Kumukahi, Cape Grim and the South Pole between 1993 and 1997 were caused by the decrease in CO 2 diffusing back to the atmosphere from plant leaves.…”
Section: Isotopic Discrimination During Photosynthesismentioning
confidence: 95%
“…In global models of the isotopic budget of CO 2 , its d 18 O value is dominated by exchange with plant and soil water, and the anthropogenic component is generally neglected (Ishizawa et al, 2002). In urban air and in some continental stations, however, the anthropogenic component is likely to be significant.…”
Section: Car Exhaust and Urban Airmentioning
confidence: 99%